Experimental Investigation on Combined Cold and Heat Unit - Sun Zhigao; Wang Ruzhu (Zhileng xuebao)
A combined cold and heat system driven by a gas engine was set up, The performance of cooling and heating was tested under the nominal conditions of air conditioning. The results show that the cooling heating capacity was 476. 1 kW and 148.7 kW, respectively. Primary energy rate was about 1.9 and energy saving ratio is 37.8%, compared with the conventional cooling and heating system. The effect of the gas engine speed on cooling and heating capacity was also tested. Cooling and heating capacity of the combined system decreased with the decrease of the gas engine speed, but primary energy rate increased with the decrease of the gas engine speed. It may be suggested that the speed of the gas engine be prior to all control parameters under part - load conditions to ensure higher primary energy rate of the system.